The Implementation of Quality Management System ISO 9001 with SWOT Analysis - Witara, Ketut; Murni Kurniasari, Laksmi; Cahyo Nugroho, Dodit (ADPEBI International Journal of Business and Social Science, 2023)
As a strategic step of the local government in continuous improvement activities, this study aimed to describe the strength, weakness, opportunity and threat analysis in the implementation of QMS ISO 9001: 2015 in elements of planning in Pemerintah Negeri Rutong Kota Ambon by Planning, Implementation (Do), Evaluation (Check) and Monitoring (Action). This study used a qualitative methodology with the researcher as the main instrument. Data sources for the study were team management and documentation and it was conducted in Pemerintah Negeri Rutong Kota Ambon. Analyzing the data using descriptive qualitative analysis, verifying the accuracy of the data during in-depth interviews with the employees of state institutions to triangulate the data with the source. The results showed that the SWOT analysis of the implementation of QMS ISO 9001: 2015 is updated. in a growth strategy phase that offers tremendous opportunity and potential for improvement. Each PDCA element of QMS ISO 9001: 2015 implementation has opportunities, threats, weaknesses and strengths that can be used for the continuous improvement of Pemerintah Negeri Rutong Kota Amboni. A SWOT analysis with the following criteria can be used to implement the strategy: socio-cultural, economic, environmental, special program of integrated economy and development of tourist villages.